Communication Method in Memorizing Short Surahs at Quranic School - Mappanyompa; Affandi, Shabibah Bint Shaufit; Rahmawati, Endang; Sahwan (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2024)
Communication allows individuals to express feelings, emotions, and opinions. Without communication, it would not be possible for the process of social interaction to occur, either individually or in groups. This study explored the communication method for memorizing short surahs, especially Juz Amma, at Taman Pendidikan Quran (the Quranic school). This study uses a qualitative method with a phenomenological approach in the field, where data collection is through observation, interviews, and documentation, which then involves three components of data analysis used, namely the Miles and Huberman interactive model approach, which includes the stages of data condensation, data presentation, and concluding. This study was conducted by collecting data from 10 ustadz and 30 students who were memorizing Juz Amma within a data collection period of six months, from January to June 2024. The results of this study found that the communication methods in memorizing short surahs, especially Juz Amma in the Quran education park, are divided into four, namely 1) Verbal communication, where the ustadz and ustadzah act as communicators who convey messages and the students as communicants who receive messages and respond to messages, such as pronouncing Juz Amma verses, questions and answers about tajwid learning, and delivering sermons. 2) Non-verbal communication, kinesis (body language); through eye contact, touch, gesture, posture, emotion, facial expression, and paralinguistic (vocal); through voice quality, volume, and speed of voice when the learning and memorization process takes place. 3) Steps before memorizing Juz Amma, such as sincere intentions, managing time, and learning tajwid and Tahsin. 4) Using the correct method according to the abilities of the students, namely, the wahdah method (repeating), and the jama’ method (reading together).